Energy efficiency maximization for secure data transmission over DF relay networks - Dong Wang; Bo Bai; Wei Chen; Zhu Han (2015 IEEE International Conference on Communications (ICC), 2015)
The security requirements of data transmission over wireless networks are energy-limited in many situations. In this paper, the secure energy efficiency (EE), is defined as the ratio of the secrecy rate to the total power, and is investigated in a systematic way considering a decode-and-forward (DF) relay network with a potential eavesdropper. We maximize the secure EE subject to the individual power constraint and the minimum decoding rate constraint of the relay. To deal with the nonconvexity of the formulated problem, a fractional programming approach embedded with DC (difference of convex functions) programming is proposed to solve the problem by two-layer iterations. The key point of the proposed algorithm is to translate the primal problem into a series of convex subproblems, which can be solved by convex programming. It is verified by simulation that the proposed algorithm achieves much better secure EE than the conventional secrecy rate maximization yet with a minor performance loss measured by average secrecy rate or secrecy outage probability.